Internal Consistency and Convergent Validity of the Klontz Money Behavior Inventory (KMBI) - Colby D Taylor; Bradley Klontz; Sonya L. Britt (Journal of Financial Therapy, 2016)
The Klontz Money Behavior Inventory (KMBI) is a standalone, multi-scale measure than can screen for the presence of eight distinct money disorders. Given the well-established relationship between mental health and financial behaviors, results from the KMBI can be used to inform both mental health care professionals and financial planners. The present study examined the internal consistency and convergent validity of the KMBI, through comparison with similar measures, among a sample of college students (n = 232). Results indicate that the KMBI demonstrates acceptable internal consistency reliability and some convergence for most subscales when compared to other analogous measures. These findings highlight a need for literature and assessments to identify and describe disordered money behaviors.
Keywords: money disorders; compulsive buying disorder; financial enabling; financial dependence; hoarding disorder; gambling disorder; workaholism; money behaviors